Pengaruh Profitabilitas, Pertumbuhan Penjualan, Ukuran Perusahaan dan Ukuran Dewan Direksi terhadap Financial Distress - Rega Erlangga; Annisa Hakim Zamzami (Universitas Pamulang, 2022)
The purpose of this study is to determine the effect of profitability, sales growth, company size, and board size on financial distress using data from coal mining sub-sector companies listed on the Indonesian stock exchange for the period 2014-2019. The method used in this research is quantitative research methods with secondary data. The population of the data in this study was 26 companies. The sample was taken using the purposive sampling method. This study uses multiple linear regression analysis techniques. The results of this study indicate that (1) ROA has a significant positive effect on financial distress, (2) Sales Growth has a significant negative effect on financial distress, (3) Company size and Board of Directors size have no effect on financial distress.